Integrating ESG into Fixed Income Portfolios: A Performance and Risk Assessment - Awaluddin, Murtiadi; Bulutoding, Lince (Theoretical and Practical Research in Economic Fields, 2026)
This study examines the performance and risk characteristics of ESG-integrated fixed income portfolios compared to conventional bond portfolios from 2018 to 2025. Using monthly data from representative indices, namely the Bloomberg MSCI Global Green Bond Index (for ESG portfolios) and the Bloomberg Global Aggregate Bond Index (for non-ESG portfolios), we employ Sharpe Ratio, Sortino Ratio, and Value-at-Risk (VaR) methods to assess risk-adjusted returns. The empirical findings indicate that ESG portfolios deliver slightly lower nominal returns but exhibit lower volatility and superior downside protection. The Sharpe ratio of ESG portfolios (0.42) surpasses that of conventional portfolios (0.36), while their 95% VaR demonstrates smaller potential losses. The results confirm that ESG integration in fixed income portfolios enhances risk resilience without significantly sacrificing returns.